FUNDAMENTALS OF SKILL THEORY IN FICTION (ON THE EXAMPLE OF THE NARRATIVE GENRE) - Sarsenbaev Qonisbay Jaqsiliq uli (American Journals, 2023)
The article shows the analysis of the basics of skill theory in fiction on the example of the narrative genre with the thoughts of the author. This article also talks about the narrative genre of fiction, as well as an analysis of the opinions and works of thinkers.
Keywords: artistic image, image combination, individual style, method of expression, period, personality, character, changes in Pose, psyche, landscape, animal, naturality, vitality.